Giorgio La Pira: i capitoli di una vita - Spinoso, Giovanni (Studi e saggi, 2022)
To tell the «chapters» of life of Giorgio La Pira (Pozzallo 1904-Florence 1977), we chose to follow a chronological order. Based on meticulous research and proposing extensive unpublished documentation, we describe the many commitments that - year after year - the Professor has found himself assuming and the various fields of his action, starting from his early years in Sicily. A very young university professor of Roman Law, intellectually engaged in the fight against fascism, constituent, parliamentarian, mayor, president of the World Federation of United Cities, La Pira has characterised his testimony in all these areas with fidelity to his deep faith and with concrete attention to the least, to the poor, to the defence of work, the right to housing, of social justice; and of the basic right to freedom and peace. For each year a summary of all the Professor's activities is reported. The work is accompanied by over a thousand biographical cards and an extensive bibliography. A solid base to start new research from, and also a useful tool for reflection and study of the life and thoughts of Giorgio La Pira.